Tumor-associated fibroblasts isolated from colorectal cancer tissues exhibit increased ICAM-1 expression and affinity for monocytes - Schellerer, Vera; Langheinrich, Melanie; Hohenberger, Werner; Croner, Roland S.; Merkel, Susanne; Rau, Tilman; Stürzl, Michael; Naschberger, Elisabeth (Oncology Reports, 2014)
Progression of colorectal cancer (CRC) is strongly associated with inflammation and other desmoplastic reactions in the tumor cell-surrounding tissue. We successfully isolated fibroblasts from the desmoplastic stroma of human CRC specimens and uninvolved colon tissue of patients treated surgically for CRC and investigated potential functional capacities. All of the isolated fibroblasts were vimentin-positive and CK-20/CD45-negative confirming the fibroblast phenotype. Differential expression patterns were detected between tumor-associated fibroblasts (TAFs) and normal tissue-associated fibroblasts (NAFs) regarding intercellular adhesion molecule-1 (ICAM-1) expression. In 11 of 12 TAF cultures, basal ICAM-1 expression was increased as compared to corresponding NAF cultures (p=0.001). After stimulation of the cultures with interleukin-1?, 8 of the 12 TAF cultures presented higher ICAM-1 levels when compared with the level in the corresponding NAF cultures (p=0.001). Moreover, the adhesive capacity of these cultures for U937 was increased in 8 out of 10 unstimulated and in 10 out of 10 stimulated cultures when TAFs and NAFs were compared. In corresponding tumor tissue sections from the same patients, the amount of ICAM-1-positive fibroblasts was significantly higher than that in the corresponding normal colon mucosa, indicating a tumor-specific effect that was maintained in the isolated cultures. These results indicate that fibroblasts from CRC tissue exhibit an increased affinity for monocytic cells. This increased intercellular interaction may contribute to elongated residence times of monocytes in CRC tissue. Therefore, these isolated fibroblasts are a useful tool for further functional investigation of desmoplastic tissue reactions in CRC.
EVALuna2:6524